Reliability of center of pressure measures during successive ski-simulated squat tasks - Moore, S. R.; Breen, S.; Kröll, J.; Strutzenberger, G.; Jensen, R. L. (ISBS Proceedings Archive (Michigan), 2019)
Laboratory assessments of alpine ski tasks have the potential to be an effective initial investigation method prior to more intensive on-snow testing. Research questions involving acute changes elicited by sport-essential equipment would be an ideal application for such investigations. The purpose of the current study was to determine the reliability of a ski-simulated squat task on centre of pressure indices. Successive squat tasks were performed in skis at a ski-simulated rhythm and analysed during four experimental conditions. Reliability analysis via repeated measures ANOVAs and intraclass correlation coefficients resulted in good to excellent reliability of centre of pressure outputs. The current study proposes a laboratory test that is reliable and encompasses biomechanical challenges presented by the alpine ski boot-binding complex.